ESTUDO DO EFEITO DO Al2O3, Fe2O3 E ZnO GERADOS A PARTIR DE NITRATOS E PECTINA CÍTRICA EM PORCELANAS ALUMINOSAS - Przybysz, Aldo (2018)
Porcelain are multiphased materials produced from natural raw material. They basically consist of kaolin, feldspar and quartz and/or alumina. It is during the sintering process that there are several chemical reactions, being affected by the temperature, time, oven atmosphere and composition of the ceramic mass. When sintered the phases present are the vitreous matrix and the crystalline phase, composed by mullite, quartz and alumina. That a small modification as much concerning in the composition from raw material a ceramic mass, may change the properties from porcelain, were addition to the mixture containing 10% of clay, 25% kaolin, 35% feldspar and 30% of alumina, quantities individually the 5% and 10% respectively the ZnO(pec) and Fe2O3(pec) originating from citrus pectin and zinc and iron nitrate respectively, and the full replacement of commercial alumina by Al2O3(pec) originating from citrus pectin and aluminum nitrate. However both originated from pectin citrus gelation plus salt the intended respective metal source. These oxides have a particular physical characteristic as high softness and high porosity. The mixture of these oxides together with the ceramic mass, which were mixed wet in balls mill, and dried in stove. The resulting powders from these mixtures were pressed and sintered. The sintered porcelains were characterized by apparent density measurement, water absorption, linear contraction, porosity percentage, Xray diffraction, scanning electron microscope, EDS microanalyses and rupture module by three points flexion. These oxides, reduced the values of the modules of rupture. Nevertheless for the major of the samples the sintering emperature was reduced. It was verified that these oxides actuate directly on the formation of the liquid stage, and it is this stage that during the sintering, modifies the other present stage and then, modify the microstructure and consequently the mechanical characteristics of the porcelain.